2000
DOI: 10.1124/mol.58.5.982
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Interaction between the HIV-Inactivating Protein Cyanovirin-N and Soluble Forms of the Envelope Glycoproteins gp120 and gp41

Abstract: The novel virucidal protein cyanovirin-N (CV-N) binds with equally high affinity to soluble forms of either H9 cell-produced or recombinant glycosylated HIV-1 gp120 (sgp120) or gp160 (sgp160). Fluorescence polarization studies showed that CV-N is also capable of binding to the glycosylated ectodomain of the HIV-envelope protein gp41 (sgp41) (as well as SIV glycoprotein 32), albeit with considerably lower affinity than the sgp120/CV-N interaction. Pretreatment of CV-N with either sgp120 or sgp41 abrogated the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…These findings explain why mannose-specific plant lectins belonging to five different plant species and two different plant families show a highly comparable crossresistance spectrum among each other, whereas there is a virtual lack of cross-resistance for these mutant virus strains with any other entry inhibitor tested, including the N-acetylglucosamine-specific lectin of Urtica dioica (data not shown). However, given the fact that cyanovirin, another selective entry inhibitor of HIV that was recently shown to prevent rectal transmission of simian-human immunodeficiency virus in macaques as a topical microbicide (40), has been characterized as a mannose-specific lectin derived from a primitive blue-green algae (10,11,28), its activity profile against several plant lectinresistant HIV-1 strains derived in our study was also determined. No cross-resistance was observed for those mutant HIV-1 strains that showed the highest degree of resistance (i.e., Ն100-fold) against HHA and GNA.…”
Section: Vol 78 2004 Hiv Resistance To Mannose-specific Plant Lectimentioning
confidence: 99%
“…These findings explain why mannose-specific plant lectins belonging to five different plant species and two different plant families show a highly comparable crossresistance spectrum among each other, whereas there is a virtual lack of cross-resistance for these mutant virus strains with any other entry inhibitor tested, including the N-acetylglucosamine-specific lectin of Urtica dioica (data not shown). However, given the fact that cyanovirin, another selective entry inhibitor of HIV that was recently shown to prevent rectal transmission of simian-human immunodeficiency virus in macaques as a topical microbicide (40), has been characterized as a mannose-specific lectin derived from a primitive blue-green algae (10,11,28), its activity profile against several plant lectinresistant HIV-1 strains derived in our study was also determined. No cross-resistance was observed for those mutant HIV-1 strains that showed the highest degree of resistance (i.e., Ն100-fold) against HHA and GNA.…”
Section: Vol 78 2004 Hiv Resistance To Mannose-specific Plant Lectimentioning
confidence: 99%
“…This region encompasses the loops between ␤1-␤2, ␤7-␤8, and ␤9-␤10 in the first binding site and between ␤6-␤7, ␤2-␤3, and ␤4-␤5 in the second binding site. In addition, notable sequence conservation is seen throughout the secondary structure elements, with residues Tyr 4 , and Tyr 120 in ␤9, and Phe 128 in ␤10 being invariant in all three sequences (all numbering refers to OAA).…”
Section: Resultsmentioning
confidence: 99%
“…The position of the pentyl is further restricted in nonamannoside by the bulk of the longer branches and might not interact favorably with the flexible loop region, lowering considerably the binding affinity of the sugar and at the same time having a chaotropic effect on the ordered molecules in the crystal. CV-N undergoes conformational changes upon binding of gp120 and gp41 (6,9,35) with an average 11% loss of ␤-sheet and 2% loss of helical structure. We attempted to determine whether this reflects in the flexibility of the loop in the uncomplexed and sugar-bound forms of CV-N by comparing the Bfactors of these structures.…”
Section: Fig 2 the Domain-swapped Cv-n Dimermentioning
confidence: 99%
“…Out of the 24 N-linked oligosaccharides found on its surface, 11 are high mannose or hybrid type (8). Studies have shown that the binding of CV-N to gp120 is carbohydrate-dependent (4,6,9). Moreover, CV-N also binds free N-linked oligosaccharides, having nanomolar affinity for the D1D3 isomer of Man-8 and oligomannose-9 (Man-9) (10 -12) and directly competing with gp120 for CV-N binding.…”
mentioning
confidence: 99%